The Development of Ecosystem Concept in Economy - O. E. Kalenov (Вестник Российского экономического университета имени Г. В. Плеханова)
The subject of the research is the idea of ‘ecosystem’ used in the economic context, which can seriously extend the possibility of interaction between organizations both with each other and with other market participants. The author studies the origin of the term and provides opinions of well-known biologists in order to substantiate similarity between natural and entrepreneurial ecosystems. The article gives an academic review of concepts by Russian and overseas researchers of ecosystems, where it is necessary to highlight theories by R. Edner, D. Isenberg, C. Wessner, G. B. Kleiner, L. Kopeykina and others. Special attention is paid to views of J. F. Moore as a founder of the concept of entrepreneurial ecosystems. Key stages of their development identified by J. F. Moore are analyzed. The author structures different scientific view and systematizes their basic characteristics. At the same time the article provides the author’s position concerning the present day understanding of the term ‘ecosystem’ with due regard to principle trends in the field of digitalization. In conclusion the author analyzes the current situation in the sphere of shaping ecosystems by Russian and overseas companies, shows preconditions of their arising and describes prospects of using the theory of ecosystems in researching economic processes.